Основні положення криміналістичної комп’ютерної візуалізації - Гусак, А.; Husak, А. (Східноєвропейський національний університет імені Лесі Українки, 2017)
В статті розглядаються основні положення застосування та роль особливого виду віртуальної візуалізації – криміналістичної комп’ютерної візуалізації. Автор розглядає значення засобів і форм візуалізації з криміналістичної точки зору і робить висновок, що криміналістична комп’ютерна візуалізація – закономірний етап розвитку даних засобів. The article examines the basic provisions of the use and role of a special type of virtual visualization – forensic visualization. The author proves the importance of means and forms of visualization from forensic point of view and concludes that forensic visualization is a logical stage in the development of these means. The author highlights such types of visualization as static and dynamic and suggests classification of criminological visualization according to various criteria: depending on the form – procedural and non-procedural; depending on the stage of criminal proceedings – at the stage of preliminary investigation and hearing the case in the court; depending on the procedural steps, in the framework of which visualization is carried out – investigation of the crime site, questioning, search, presentation for identification, investigative experiment; depending on the stage of the investigation – under preparation, at the working stage, at the final stage. The author considers preservation of this technology importance with reasonable changes in criminal procedure law to be rather efficient in resolving many issues. The study shows that in some aspects unnecessary/extra technologization of criminal proceedings may be dangerous as it may lead to the overuse of forensic animation by the participants of criminal proceeding and may cause negative impact on making an objective decision.
Basic Provisions of the Forensic Computer Visualization
Keywords: криміналістична візуалізація; технічні засоби; місце злочину; фото-, відеозйомка; 3D-моделювання; forensic visualization; technical means; scene of crime; photo-video shooting; 3Dmodeling